Supramolecular imprinted sensor for carbofuran detection based on a functionalized multiwalled carbon nanotube-supported Pd-Ir composite and methylene blue as catalyst. (10th January 2016) - Li, Shuhuai; Yin, Guihao; Wu, Xuejin; Liu, Chunhua; Luo, Jinhui
Abstract: A novel supramolecular imprinted electrochemical sensor was developed for carbofuran (CBF) determination based on a multiwalled carbon nanotube-supported Pd-Ir nanocomposite catalyst (MWCNT/Pd-Ir) with methylene blue (MB) signal amplification. First, MWCNT/Pd-Ir composite nanoparticles were synthesized and used to modify the surface of a glassy carbon electrode; then, a molecular imprinted polymer for CBF was prepared by electropolymerization, with MB-doped o -phenylenediamine as the functional monomer and a 4-tert-butylcalix[8]arene-CBF (4TB[8]A-CBF) supramolecular complex as the template. The electrical signals were controlled though the elution and re-adsorption of CBF. Due to the double catalysis by the MWCNT/Pd-Ir and MB, the current intensity for CBF was obviously amplified. Additionally, because of the double recognition by the 4TB[8]A and MIP, the sensors showed outstanding CBF identification properties. The method was applied to detect CBF in agricultural products, and the satisfactory results were obtained.